2017
DOI: 10.18203/2349-2902.isj20164847
|View full text |Cite
|
Sign up to set email alerts
|

The problem of burns

Abstract: Background: Burns due to accidents are a common cause of morbidity and mortality in the Indian sub-continent. The causes being preventive, warrant a better understanding of the epidemiology to know the seriousness of the situation, implement better medical care and prevent such accidents. Aim was to study the morbidity and mortality related to percentage of burns.Methods: This is a retrospective observational study where patients admitted with burns 2013 and 2015 were evaluated. Data with respect to sex, age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…13) This may be due to fact that males are more exposed to the industrial work and other fire causing activities like smoking.Whereas, our findings are relatively inconsistent to the studies conducted in other south Asian countries that reported female predominance. (14,15) The females are mostly burnt due to household explosions or cooking oil burns. Main reasons are inexperience with cooking, use of risky fire appliances and use of conventional synthetic clothing that catch fire quickly as well as spread it throughout the body of victim.…”
Section: Discussionmentioning
confidence: 99%
“…13) This may be due to fact that males are more exposed to the industrial work and other fire causing activities like smoking.Whereas, our findings are relatively inconsistent to the studies conducted in other south Asian countries that reported female predominance. (14,15) The females are mostly burnt due to household explosions or cooking oil burns. Main reasons are inexperience with cooking, use of risky fire appliances and use of conventional synthetic clothing that catch fire quickly as well as spread it throughout the body of victim.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results are reported from studies conducted in India and abroad. [6][7][8][11][12][13][14] Mean total body surface area (TBSA) was 36.09%. Mean TBSA reported by Jain M et al, was 45.33%, and in Egypt, Hemeda et al, reported mean TBSA 32±5.7% similar to our study.…”
Section: Discussionmentioning
confidence: 99%